2020
DOI: 10.1097/sga.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Educational Video on the WeChat Platform Can Effectively Improve the Quality of Bowel Preparation

Abstract: Bowel preparation is a core issue in the quality of colonoscopy. We attempted to investigate whether an educational video via WeChat (a widely used mobile social media app) improved the compliance of patients and quality of bowel preparation. We enrolled 198 colonoscopy patients aged 35–70 years. They were randomly divided into the WeChat group (100 cases) and the control group (98 cases). The outcomes were the compliance of patients in the bowel preparation process and quality of the bowel preparation accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The four included studies all used an internationally standardized bowel preparation quality assessment scale to evaluate the quality of bowel preparation. Three studies used the BBPS, 14–16 and the heterogeneity test showed no significant heterogeneity ( P = .24, I 2 = 29%). Therefore, the fixed effects model was used for the combined analysis.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The four included studies all used an internationally standardized bowel preparation quality assessment scale to evaluate the quality of bowel preparation. Three studies used the BBPS, 14–16 and the heterogeneity test showed no significant heterogeneity ( P = .24, I 2 = 29%). Therefore, the fixed effects model was used for the combined analysis.…”
Section: Resultsmentioning
confidence: 95%
“…One study used the WeChat public number for bowel preparation education and automatically pushed multimedia messages with detailed information to patients' WeChat app 2 days before the colonoscopy 16 . The other provided an educational video of approximately 8 minutes in duration via WeChat platform 15 . Three included studies used the BBPS to evaluate the quality of bowel preparation, 14–16 and the other study used the OBPS 13 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations